Evaluation of the Implementation of the Payroll Accounting System at KJPP SISCO - Fitri Dwi Jayanti; Sri Trisnaningsih (International Journal Business, Management and Innovation Review, 2025)
The era of globalization that has penetrated into all aspects is enough to affect the sustainability of the company, especially in determining operational costs to be more effective and efficient. Company operations include the amount of salary given to employees. Salary is a financial consideration that must be paid to employees for their contribution to the organization, so it is necessary to ensure that salary payments are structured to achieve operational efficiency. To achieve this, management must set up a payroll system. SISCO Public Appraisal Services Office evaluates the implementation of the payroll system for the better and to ensure that payroll is processed effectively and efficiently. However, there is still a problem that there are uncollected receivables from clients that hamper the receipt of employee salaries. The purpose of this paper is to evaluate the application of the payroll accounting system at the SISCO Public Appraisal Services Office. The data collection methods in this paper are observation, interview, and documentation. The results obtained are in the form of increased skills in accounting, especially regarding the payroll accounting system and its application in the agency. The payroll accounting system must be designed in such a way that it does not hamper the company's operations.